Language Change in the Digital Era: Social Media, Globalization, and Technological Impacts on Language Evolution - Paramata, Yurizka; Bolilio, Ayida Muzdalifah; Ahmad, Revalya; Lundeto, Afrizal (Lembaga Publikasi Ilmiah Dwipantara, 2025)
Language is a dynamic entity that continuously adapts to societal changes, especially in the 21st century with the rise of digital communication platforms like social media, instant messaging, and online communities. This digital environment, coupled with globalization and technological advancements, has fostered the evolution of new language patterns, vocabularies, and communication norms. Digital media not only alters how language is used but also redefines what constitutes language itself, contributing to the democratization of language where individuals from diverse backgrounds influence its development. This research aims to analyze the socio-cultural and linguistic impact of digital technologies and global networks on language evolution by examining real-life language use across digital platforms. Employing a qualitative approach with a library research method, data was collected through a literature review of academic sources such as books, scientific journals, articles, and publications discussing language change in the digital era. The analysis involved reviewing and comparing theories and findings from previous research to identify common patterns in language evolution. Key findings indicate five main themes: lexical innovation, code-switching, grammar simplification, the increased use of emojis and GIFs, and the emergence of globalized vernaculars. These changes align with technolinguistics, where technology actively shapes language, and Darwinian adaptation theory, where language evolves in response to social and communication demands, prioritizing efficiency and relevance.